Effects of natural products on macrophage immunometabolism: A new frontier in the treatment of metabolic diseases - Jiani Li; Chen Guo; Xiaofei Yang; Weinan Xie; Wenjing Mi; Chenglong Hua; Cheng Tang; Han Wang (Pharmacological Research)
Immunometabolic variations in macrophages critically influence their differentiation into pro-inflammatory or anti-inflammatory phenotypes, thereby contributing to immune homeostasis, defense against infection, and tissue repair. Dysregulation of macrophage immunometabolism has been closely implicated in several metabolic diseases, including obesity, type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD), hypertension, atherosclerosis, and gout, which positions macrophages as potential therapeutic targets. Recently, several natural products that target macrophage metabolic pathways have shown significant efficacy in managing metabolic diseases; however, a systematic review of these findings has yet to be conducted. This study consolidates natural products with immunoregulatory properties, including flavonoids, phenols, terpenoids, and naphthoquinones, which can alleviate chronic inflammation associated with metabolic disorders by modulating macrophage metabolic pathways, such as aerobic glycolysis, oxidative phosphorylation (OXPHOS), and fatty acid oxidation (FAO). This review aims to elucidate the metabolic regulation of the immune system, analyze metabolic alterations in macrophage associated with metabolic diseases, and summarize the beneficial roles of natural products in immunometabolism, providing novel insights for the prevention and therapeutic management of metabolic diseases.